The Tomato DELLA Protein PROCERA Acts in Guard Cells to Promote Stomatal Closure. Issue 12 (17th November 2017) - Nir, Ido; Shohat, Hagai; Panizel, Irina; Olszewski, Neil; Aharoni, Asaph; Weiss, David
Abstract : The tomato DELLA protein PROCERA, a negative regulator of gibberellin signaling, increases the sensitivity of guard cells to abscisic acid, leading to stomatal closure and increased drought tolerance. Abstract: Plants employ stomatal closure and reduced growth to avoid water deficiency damage. Reduced levels of the growth-promoting hormone gibberellin (GA) lead to increased tolerance to water deficit, but the underlying mechanism is unknown. Here, we show that the tomato ( Solanum lycopersicum ) DELLA protein PROCERA (PRO), a negative regulator of GA signaling, acts in guard cells to promote stomatal closure and reduce water loss in response to water deficiency by increasing abscisic acid (ABA) sensitivity. The loss-of-function pro mutant exhibited increased stomatal conductance and rapid wilting under water deficit stress. Transgenic tomato overexpressing constitutively active stable DELLA proteins (S- della ) displayed the opposite phenotype. The effects of S- della on stomatal aperture and water loss were strongly suppressed in the ABA-deficient mutant sitiens, indicating that these effects of S- della are ABA dependent. While DELLA had no effect on ABA levels, guard cell ABA responsiveness was increased in S- della and reduced in pro plants compared with the wild type. Expressing S- della under the control of a guard-cell-specific promoter was sufficient to increase stomatal sensitivity to ABA and to reduce water loss under water deficit stress but had no effect on leaf size. This result indicates that DELLA promotes stomatal closure independently of its effect on growth.